Ultra-Reliable Low-Latency Communication (URLLC) in 5G Networks: Enabling Mission-Critical Applications - Ying, Deng; Shajahan, Mohamed Ali; Khair, Md Abul; Sandu, Arun Kumar (Engineering International, 2023)
In 5G networks, Ultra-Reliable Low-Latency Communication (URLLC) is a critical technology that supports mission-critical applications in various industry sectors. This study investigates the importance, difficulties, and policy consequences of URLLC deployment. A thorough assessment of the literature, an analysis of the underlying technologies, performance evaluation methods, and the effect of URLLC on mission-critical systems are all part of the process. Principal discoveries underscore the revolutionary possibilities of URLLC in healthcare, transportation, industrial automation, and public safety. However, they also point to obstacles to technological optimization, spectrum distribution, security, and interoperability. The significance of proactive steps in spectrum policy, regulatory frameworks, data protection, and research funding is highlighted by policy implications as they aid in successfully implementing URLLC. Stakeholders may fully realize the potential of URLLC to build a connected world where incredibly dependable communication enables people, companies, and communities to prosper and innovate in the digital era by tackling these issues and accepting policy actions.
Keywords: URLLC; 5G Networks; Low-Latency Communication; Mission-Critical Applications; Ultra-Reliable Communication; Network Reliability